Organic molecule electrode with high capacitive performance originating from efficient collaboration between caffeic acid and graphene & graphene nanomesh hydrogel. (5th December 2019) - Wang, Xiaotong; Hou, Lijie; Chen, Wenlian; Xie, Yandong; Xie, Kefeng; An, Ning; Hu, Zhongai
Abstract: The present work reports an organic molecule electrode (OME) based on the graphene and graphene nanomesh (GNM) hydrogel non-covalently functionalized by caffeic acid (CFA) molecules (denoted as G&GMH-CFA). In such electrode system, the three-dimensional conductive network has a cross-linking channel constructed by means of the in-plane pores on the graphene nanomesh, which is benefit for exposing more active sites accessible to electrolyte and accordingly enhancing supercapacitive behaviors of the OME. The G&GMH-CFA delivers a specific capacitance of 482.6 F g −1  at current density of 1 A g −1 . And it is noted that the Faraday current response peaks are located in the positive potential range of 0.6 V, which is superior to the organic molecules electrode reported in the correlative works. In addition, the density functional theory (DFT) calculations are used to illuminate the core issue of charge storage mechanism and binding interactions between CFA and graphene. To match with the resultant positive electrode, AQ functionalize graphene-like nanoflower (CNF-AQ) was prepared as counterpart (negative) electrode. The assembled asymmetric supercapacitors (ASC) CNF-AQ//G&GMH-CFA2 could exhaustively release the supercapacitive performance due to match and self-coordination based on the reasonable matching of two electrodes in structure, charge quantity and kinetics during the electrochemical energy storage process. The CNF-AQ//G&GMH-CFA2 delivered energy density of 26.4 Wh kg −1  at the power density of 0.7 kW kg −1 . Two tandem CNF-AQ//G&GMH-CFA2 devices could easily light 88 LEDs. Graphical abstract: The organic molecule electrode is fabricated by the CFA functionalized graphene hydrogel with plentiful transport channels inside of the conductive skeleton, matching with CNF-AQ to assemble full-carbon ASC could easily light 88 LEDs.Image 1